Inter Alia: Johan Cilliers and the homiletical imagination - Campbell, Charles L (Stellenbosch Theological Journal, 2019)
This essay will explore the homiletical imagination through one of Johan Cilliers’ favourite phrases: inter alia (“among other things”). The phrase captures the unsettled restlessness not only of Cilliers himself, but of homiletics. Homiletics really has no centre; it can never close in on itself because there is literally no there there. Homiletics is an “among-other-things” discipline. It exists only among many other disciplines; it depends on the connections it makes with biblical studies and theology and history and rhetoric and performance. But that is just the beginning. For the homiletical imagination comes alive only as it makes these same connections with virtually everything: the Karoo or a garden or a joke; a photograph or a painting or graffiti; jesters, clowns, iimbongi. The homiletical imagination lives inter alia. It ceaselessly plays among other things, restlessly exploring multiple connections as it seeks inspiration and understanding. Through his extraordinary work, Johan Cilliers models this kind of imagination and invites all homileticians to a richer understanding of what we do.